Pelaksanaan Tanggung Jawab Sosial Perusahaan Pada BPR di Kabupaten Badung - I Putu Bayu Pramana; I Made Arjaya; Desak Gede Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—The company is a place where it aims to improve the lives of the people. In its development in the economic and business sectors the role of the company in terms of improving the country's economy is a responsibility of each company, in this case it is called corporate social responsibility (CSR). In this study, focusing on the implementation of CSR in BPR in Badung Regency, where the BPR is expected to be able to prosper the surrounding community and carry out the mandate of the PERDA of Badung Regency No. 6 of 2013 concerning Corporate Social Responsibility. From this background two problems can be formulated, namely: 1). What is the regulation of social responsibility (CSR) in the annual BPR activity plan in Badung Regency? 2). What is the implementation of the annual activity plan that regulates social responsibility (CSR) in rural banks in Badung Regency? the method used is empirical research method, which is research directly in the field. The results of this are social responsibility is the company's commitment to improving the economy of the community that benefits the company and the general public, where the regulation of corporate social responsibility in BPR in Badung Regency is Law No. 40 of 2007 concerning Limited Liability Companies, PP No. 47 of 2012, and Badung District Regulation No. 6 of 2013. In its implementation social responsibility (CSR) in BPR in Badung Regency has been running well as in terms of education providing scholarships to outstanding students and the introduction of banking products to the local community.